TB Meningitis and TB Peritonitis: Abdominal Pseudocyst and VP-Shunt Link - Ahmed, Manzoor (Case Rep Radiol, 2019)
TB meningitis (TBM) carries high morbidity and mortality and is a relatively common extrapulmonary TB in the third world countries. TBM as thick exudative disease manifests on MRI and CT as nodular basal leptomeningitis, hydrocephalus, basal infarcts, and tuberculomas. Hydrocephalus is treated with ventriculoperitoneal shunting (VPS). Shunt malfunction and revision are common. We report a case of multidrug-resistant TBM with spinal involvement and dissemination of the disease via VPS causing TB peritonitis (TBP). TBP presented as a large abdominal pseudocyst around the catheter tip with shunt malfunction. There was no evidence for any other site of extra-CNS disease. TBP per se is relatively less common. This is the first case reporting VPS as a means of TB spread.